MICROPROPOGATION OF HIBISCUS ROSA SINENSIS (L.) - SUMAN KUMARI; R. K. PANDEY (The Bioscan, 2011)
Hibiscus rosa sinensis L. commonly known as China rose is an ornamental plant belonging to family Malvaceae. This is a sacret plant with great economic importance as medicinal plant. Differentiation of shoots were initiated on Murashige and Skoog (1962) medium supplemented with various combination of phytohormones such as IAA, IBA, NAA, KN, BAP and 2,4-D.